2014
DOI: 10.1088/0004-637x/788/2/187
|View full text |Cite
|
Sign up to set email alerts
|

Subarcsecond Imaging of the NGC 6334 I(n) Protocluster: Two Dozen Compact Sources and a Massive Disk Candidate

Abstract: Using the Submillimeter Array (SMA) and Karl G. Jansky Very Large Array, we have imaged the massive protocluster NGC 6334 I(N) at high angular resolution (0. 5 ∼ 650 AU) from 6 cm to 0.87 mm, detecting 18 new compact continuum sources. Three of the new sources are coincident with previously identified H 2 O masers. Together with the previously known sources, these data bring the number of likely protocluster members to 25 for a protostellar density of ∼700 pc −3 . Our preliminary measurement of the Q-parameter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(100 citation statements)
references
References 121 publications
6
93
1
Order By: Relevance
“…(Cyganowski et al 2011(Cyganowski et al , 2012. However, maser emission of the CH 3 OH(4 2,2 -3 1,2 ) transition at 218.440 GHz has, to our knowledge, only been tentatively detected in DR21 (OH) by Zapata et al (2012) and in NGC 6334 I(N) by Hunter et al (2014) prior to this work. Population inversion for the 218.440 GHz transition has been predicted in maser models (Voronkov et al 2012).…”
Section: Millimeter Methanol Maser Emissionmentioning
confidence: 64%
“…(Cyganowski et al 2011(Cyganowski et al , 2012. However, maser emission of the CH 3 OH(4 2,2 -3 1,2 ) transition at 218.440 GHz has, to our knowledge, only been tentatively detected in DR21 (OH) by Zapata et al (2012) and in NGC 6334 I(N) by Hunter et al (2014) prior to this work. Population inversion for the 218.440 GHz transition has been predicted in maser models (Voronkov et al 2012).…”
Section: Millimeter Methanol Maser Emissionmentioning
confidence: 64%
“…NGC 6334 I(N), hereafter simply I(N), is an IRDC at a distance of 1.3 kpc and displays seven compact millimetre continuum sources within a projected diameter of 0.1 pc at 2 resolution. In addition, in their study Hunter et al (2014) find 25 likely protostellar objects associated within a physical radius of 0.21 pc at 1.3 mm.…”
Section: The Future Of Sdc335mentioning
confidence: 89%
“…A second comparable region is the NGC 6334 I(N) protocluster, which has been well studied at mm wavelengths, most recently by Hunter et al (2014). NGC 6334 I(N), hereafter simply I(N), is an IRDC at a distance of 1.3 kpc and displays seven compact millimetre continuum sources within a projected diameter of 0.1 pc at 2 resolution.…”
Section: The Future Of Sdc335mentioning
confidence: 99%
“…We note that Ilee et al (2016), Johnston et al (2015) and Chen et al (2016) identify Keplerian rotation in their observations of massive discs. However the observational measurements of the disc kinematics are complicated by the fact that they are obtained from molecular line tracers that may also simultaneously probe the rotating and infalling envelopes (for example Hunter et al (2014) observed a combination of Keplerian rotation and infall). In order to make a more realistic comparison between the model and observations it is necessary to compute synthetic observations from the model and test the model more directly via molecular line profiles (see Section 5.5).…”
Section: Disc Mass and Radiusmentioning
confidence: 99%